On simplifying the structure of labour demand: an analysis of the DOT data - Wim P. M. Vijverberg; Joop Hartog (Institute for the Study of Labor (IZA), 2005)
We analyse the information in the Dictionary of Occupational Titles to characterize the structure of labour demand. Two dimensions, an intellectual factor and a dexterity factor capture most variation in job requirements. Job complexity in relation to Things correlates highly with the dexterity factor. Complexity in relation to Data is intricately interwoven with most other dimensions of jobs. Remarkably, while complexity in relation to Data and to Things associates with extensive training, this does not hold for complexity in relation to People. There is no dichotomy between mathematical and verbal required skills. Poor working conditions are not the exclusive prerogative for workers in low level jobs. This independence provides a good setting for testing the theory of compensating wage differentials and indeed we find a good deal of support.
Keywords: J21; J23; J31; 330; labor demand structure; job requirements; compensating differentials